ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KEHAMILAN PADA REMAJA - Deasy Elvianita; Vivin Indrianita; Mytha Pondaang (Jurnal Medicare, 2026)
Teenage pregnancy has a negative impact on reproductive health, psychology, social aspects, and the sexual behavior of adolescents. In 2022, BKKBN released data showing 15,212 applications for marriage dispensation in East Java, with one of the largest contributing districts being Probolinggo Regency. This research aims to identify and analyze various factors that contribute to the occurrence of teenage pregnancy in Probolinggo Regency. The study uses a qualitative method with a case study design. Participants in this study were female adolescents aged 15-19 years with a history of pregnancy and childbirth that occurred in 2024 - 2025. The main subjects were 15 adolescents, the supporting subjects (the adolescents' parents) were 15 people, and the school principals were 4 people. Data collection was conducted through in-depth interviews. The research results showed that several factors were found to cause teenage pregnancy, including risky premarital sexual behavior, low knowledge of reproductive health, the role of schools, and the parenting style applied by parents to their children. The factors that influence the occurrence of teenage pregnancy include age, with the majority being 16 years old. Most teenagers' last level of education is junior high school, most parents work as farmers, and on average, parents' last level of education is no schooling. It is necessary to integrate schools and parents regarding reproductive health literacy and education for teenagers, as well as actively involving parents in building more open communication with their teenage children.